2019
DOI: 10.1073/pnas.1715272116
|View full text |Cite
|
Sign up to set email alerts
|

Long-term expansion and differentiation of adult murine epidermal stem cells in 3D organoid cultures

Abstract: Mammalian epidermal stem cells maintain homeostasis of the skin epidermis and contribute to its regeneration throughout adult life. While 2D mouse epidermal stem cell cultures have been established decades ago, a long-term, feeder cell- and serum-free culture system recapitulating murine epidermal architecture has not been available. Here we describe an epidermal organoid culture system that allows long-term, genetically stable expansion of adult epidermal stem cells. Our epidermal expansion media combines aty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 58 publications
1
66
0
Order By: Relevance
“…It appears that Epi-SCs preserve their memory to form a stratified layer resembling the epidermis in culture and after transplantation into excisional wounds. This ability could be well preserved in the cells even after a longterm culture expansion [32]. In the present study, we found that Epi-SCs could migrate to form a distinctive epidermis-like layer over the "dermis" when cultured in mixture with SKPs in Matrigel.…”
Section: Discussionsupporting
confidence: 58%
“…It appears that Epi-SCs preserve their memory to form a stratified layer resembling the epidermis in culture and after transplantation into excisional wounds. This ability could be well preserved in the cells even after a longterm culture expansion [32]. In the present study, we found that Epi-SCs could migrate to form a distinctive epidermis-like layer over the "dermis" when cultured in mixture with SKPs in Matrigel.…”
Section: Discussionsupporting
confidence: 58%
“…Human skin tissue samples were obtained from Chinese PLA General Hospital, and ethical approval and informed consent were obtained. The interfollicular epidermal stem cells were isolated as described [ 19 , 20 ] with some modifications. Briefly, subcutaneous tissues and fat were removed and the tissues were digested with Dispase II (2.5 mg/mL, Cat #17150041, Gibco) at 37 °C for 2 h to obtain the epidermal sheets.…”
Section: Methodsmentioning
confidence: 99%
“…To avoid this potential risk, chemically defined culture media without animal-derived ingredients have been developed and are commercially available [24]. These feeder-and serum-free media [25] enable clonal growth and serial culture of EPSCs, but it is still unclear whether they can maintain EPSCs for long periods ex vivo.…”
Section: Expansion Of Epscs In Vitromentioning
confidence: 99%